Performance Analysis of Waste Glass Shredder Machine: Real Effort to Process Construction Materials Waste - Abdullah, Sirajuddin Haji; De Side, Gagassage Nanaluih; Amuddin, Amuddin; Priyati, Asih; Fuadi, Mi'raj (Indonesian Green Technology Journal, 2023)
Glass waste is one of the residual waste construction materials that can be recycled by turning its particles into smaller sizes so that the processing of glass waste will be easier, especially in terms of safety. This study aims to test the performance and performance of glass waste crushing machines, determine the rotation speed of the shredder gear in glass waste crushing machines and to determine the production efficiency of glass waste crushing machines. This research uses experimental methods with field experiments, by analyzing the machine directly. The parameters observed were testing the feasibility of tool performance by looking at the results of glass waste shredding, the production efficiency of the glass waste shredder and knowing the rotation speed of the crushing gear in the glass waste shredder. The results showed that glass waste with a thickness of 0.2 cm that had been crushed obtained an average value of 1405.2 grams and for a thickness of 0.5 cm, 1376.2 grams. At the speed of rotation of the glass waste crusher gear, the average value obtained by glass with a thickness of 0.2 cm is more than glass with a thickness of 0.5 cm, namely 16.98 rpm while glass with a thickness of 0.5 cm is 13.82 cm. The results of the calculation of the production efficiency of the glass waste shredder with a thickness of 0.2 cm have the highest result at the 5th repetition of glass entry, that is 94.80% and the lowest at the 1st repetition is 92.53%, and for glass with a thickness of 0.5 cm the highest result is obtained at the 2nd repetition of glass entry, that is 92.66% and the lowest result at the 1st repetition is 89.66%. Keywords: glass shredder machine, glass waste, waste processing, performance test, waste materials